Redefining risk of contralateral cervical nodal disease in early stage oropharyngeal cancer in the human papillomavirus era. Issue 5 (21st January 2021) - Smith, Andrew W.; Gallitto, Matthew; Lehrer, Eric J.; Wasserman, Isaac; Gupta, Vishal; Sharma, Sonam; Liu, Jerry T.; Posner, Marshall; Misiukiewicz, Krzysztof; Westra, William H.; Genden, Eric M.; Haidar, Yarah; et al.
Abstract: Background: The optimal extent of surgery and/or radiation to the contralateral lymph node region is unknown in early‐stage human papillomavirus (HPV)–related oropharyngeal squamous cell carcinoma (OPSCC). Methods: To investigate the pathologic incidence of and risk factors for contralateral nodal disease (CND) in cT1‐T2 HPV‐related OPSCC treated with transoral robotic surgery (TORS) and bilateral neck dissection (BND), the records of 120 patients were reviewed. Results: Eleven patients displayed pathologic contralateral nodal disease (pCND), including 7.1% of tonsil and 10.9% of base of tongue (BOT) cases. Medial hemistructure involvement and cN2 disease were significantly associated with pCND. Zero cN0 patients had pCND, and on multivariate analysis only cN classification remained significantly associated with pCND. Four percent of BOT patients and 2% of tonsil patients with a well‐lateralized primary and cN0/N1 neck demonstrated pCND. Conclusions: HPV‐related OPSCC that are cN0‐N1 have exceedingly low rates of pCND. Well‐lateralized HPV‐related BOT primaries with limited clinical nodal disease may be candidates for ipsilateral only treatment.